2020
DOI: 10.1002/bab.1917
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of thermosensitive hydrogel based on quaternized chitosan for intranasal delivery of insulin

Abstract: Nasal administration is a form of systemic administration in which drugs are insufflated through the nasal cavity. Steroids, nicotine replacement, antimigraine drugs, and peptide drugs are examples of the available systematically active drugs as nasal sprays. For diabetic patients who need to use insulin daily, the nasal pathway can be used as an alternative to subcutaneous injection. In this regard, intranasal insulin delivery as a user‐friendly and systemic administration has recently attracted more attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The use of CS in combination with Carbopol 934, poloxamer 407, sodium carboxymethylcellulose and hydroxypropyl methylcellulose, allowed the development of an in situ gel for nose-to-brain delivery of rivastigmine tartrate, which showed a three-times increase of the drug permeation through the nasal membrane and a 3.4-times higher distribution to the brain compared to the simple drug solution [ 158 ]. The use of a mixture of CS, quaternized CS and gelatin allowed the obtaining of a thermosensitive hydrogel with low gelation time, suitable swelling ratio and extended release of insulin up to 24 h, thus demonstrating the potential application of the formulation to improve the absorption of hydrophilic macromolecular drugs through the nasal route [ 159 ].…”
Section: Chitosan-based Mucosal Drug Delivery Systemsmentioning
confidence: 99%
“…The use of CS in combination with Carbopol 934, poloxamer 407, sodium carboxymethylcellulose and hydroxypropyl methylcellulose, allowed the development of an in situ gel for nose-to-brain delivery of rivastigmine tartrate, which showed a three-times increase of the drug permeation through the nasal membrane and a 3.4-times higher distribution to the brain compared to the simple drug solution [ 158 ]. The use of a mixture of CS, quaternized CS and gelatin allowed the obtaining of a thermosensitive hydrogel with low gelation time, suitable swelling ratio and extended release of insulin up to 24 h, thus demonstrating the potential application of the formulation to improve the absorption of hydrophilic macromolecular drugs through the nasal route [ 159 ].…”
Section: Chitosan-based Mucosal Drug Delivery Systemsmentioning
confidence: 99%
“…Chitosan is a cationic polysaccharide derived from chitin and is made up of diglucose amine and N-acetyl glucose amine groups [ 81 , 82 , 83 ]. Antibiotics [ 81 , 83 ], antivirals [ 84 ], and immunosuppressants [ 85 ] have been delivered using chitosan.…”
Section: Natural Biopolymer Scaffolds For Therapeutic Ev Deliverymentioning
confidence: 99%
“…Antibiotics [ 81 , 83 ], antivirals [ 84 ], and immunosuppressants [ 85 ] have been delivered using chitosan. Additionally, chitosan has been utilized to deliver insulin [ 82 ] and genetic material [ 86 , 87 , 88 ].…”
Section: Natural Biopolymer Scaffolds For Therapeutic Ev Deliverymentioning
confidence: 99%
“…The authors concluded that gel: Ch-HTCC (1:6) consisting of 2 wt% chitosan, 1 wt% HTCC, and 0.5 wt% Gel provides the best results with a prolonged release of insulin rate. This formulation could be used in the future for delivery of insulin in a controlled release and for a prolonged time [ 85 ]. In Vivo …”
Section: Advancements In Insulin Delivery Technologymentioning
confidence: 99%